Prolonged postoperative urine leakage due to a calyceal diverticulum mimicking a renal cyst: A case report and literature review - Yu, Jun-jie; Yang, An-qi; Du, Yong-jun; Huang, Tian-bao (Frontiers in Surgery, 2022)
Background Calyceal diverticulum is a rare cystic cavity that communicates with the collecting system via a narrow neck or infundibulum. In clinical practice, part of the calyceal diverticula is difficult to differentiate from simple renal cysts even after contrast-enhanced CT. To date, there are few literatures on the diagnosis and treatment of calyceal diverticulum combined with renal pelvis dilatation, especially with regard to the treatment of prolonged post-operative urine leakage. Case Description A 53-year-old woman with calyceal diverticulum and renal pelvis dilatation mimicking a simple renal cyst suffered urine leakage after receiving laparoscopic unroofing of renal cyst. A persistent urine leakage was observed immediately after surgery, with about 200 mL drainage fluid per day. We firstly attempted to place a Double-J ureteral stent and indwell catheter. After failed that, a conservative treatment was performed. The core idea of the conservative treatment is retaining the drainage tube for more than 1 month, and then clamping the drainage tube for 1 week and finally removing the drainage tube. By three weeks’ follow-up, the urine leakage was totally disappeared and CT scan showed hydronephrosis of the right kidney without perirenal exudation and lower pole cyst of the right kidney shrank significantly. Conclusions Here, this case we reported is to attract the attention of clinicians. Renal cysts should exclude the possibility of the calyceal diverticulum. If urine leakage is inevitable after surgical treatment, our conservative treatment strategy is also an alternative method.